Innovation of Bulletin Media in the Form of Pocket Book to Improve Students’ Conceptual Understanding of Green Chemistry - Vita Ayu Wandira; Abdul Gani; Evendi Evendi; Nur Aziani Binti Hermanto; Muhammad Nazar; Ratu Fazlia Inda Rahmayani (Journal of Innovation in Educational and Cultural Research, 2024)
Bulletins in the form of pocketbooks are one solution to help students master the conceptual understanding of green chemistry material in the emancipated curriculum. This research aims to develop a bulletin in the form of a pocketbook to increase students' understanding of concepts. Analysis, design, development, implementation, and evaluation are all included in the ADDIE model, which is used in this research together with the research and development technique. The sampling technique used simple random sampling. The population was 10th-grade students of senior high school in Banda Aceh. The results of the student response questionnaire show that the bulletin's attractiveness in the form of a pocketbook is 84.29%. The innovation of a bulletin in the form of a pocketbook has a good concept understanding ability based on the t-test value of 0.001 0.05. This research concludes that the bulletin in the form of a pocketbook is more effective than textbooks in teaching green chemistry. Bulletins in the form of practical and appropriate pocketbooks can improve students' understanding of concepts. Using bulletins in pocketbooks can be a reference and achievement for chemistry teachers' learning in learning activities in the emancipated curriculum.